Assessment of human health risks posed by toxic heavy metals in Tilapia fish (Oreochromis mossambicus) from the Cauvery River, India - Gupta, Nikita; Arunachalam, Sathiavelu (Frontiers in Public Health, 2024)
Heavy metal toxicity is a serious threat to human health due to its bioaccumulation, biomagnification, and persistent nature in the environment including aquatic systems. In the recent past, heavy metal contamination in the environment has occurred due to various anthropogenic sources. The concentration of potentially toxic heavy metals was determined by Atomic Absorption Spectroscopy in Tilapia (Oreochromis mossambicus), a highly farmed and consumed fish species in southern parts of India. The mean levels of Fe were found to be higher in major organs of the fish with the highest levels in liver (Mean 1554.4 ± 1708.7 mg/kg) and lowest in the muscles (Mean 130.757 ± 33.3 mg/kg). Correlation Matrix analysis revealed relationships between the occurrence of various heavy metals in different organs of fish and indicated similar origins and chemical properties. Target hazard quotient for Cd, Co, Pb, and Cr in the Liver, Co and Cr in the Gills, and Co in Muscle were > 1 for adults, which showed a significant health risk from the combined effects of these metals. The potential health risk to humans, according to the cancer risk (CR) assessment is attributed mainly to Cd and Cr levels. Overall, moderate fish consumption is advised to limit the bioaccumulation of heavy metals over prolonged exposure and associated health risks.